Karakteristik Mineralogi Batubara Desa Tiktok Kecamatan Baraka Kabupaten Enrekang: Mineralogical Characteristics of Coal in Tiktok Village, Baraka District, Enrekang Regency - Firaldy S; Budiman, Agus Ardianto; Thamsi, Alam Budiman (CV Insight Publisher, 2025)
Coal is a solid, combustible sedimentary rock formed from the decay of ancient plants. Coal is brown to black in color and undergoes physical and chemical changes that increase its carbon content. The purpose of this study was to determine the mineral composition of the coal in the area. The sampling method used channel sampling, based on research conducted using XRD, obtained results: the upper sample was composed of quartz (69.8%), graphite (30.2%), the middle sample was composed of quartz (37.6%), graphite (33.8%), and albite (28.8%), and the lower sample was composed of albite (41.2%), quartz (30.0%), and graphite (28.8%).